Sobre el papel del latín y el concepto de latinismo desde la perspectiva española y polaca - Pawlak, Aneta (Collectanea Philologica, 2022)
The objective of the article is twofold. On the one hand, it aims to briefly outline the history of the Spanish and the Polish language in order to compare the role of Latin in the formation of both languages. On the other hand, it focuses on the lexicological terminology related to Latin-derived words, with special focus on Latinisms. In addition to the lexicological nomenclature, classifications of Latinisms are also compared. The differences detected in the contrastive analysis mainly concern the lack of heritage words from Latin in Polish and the different concept of doublets in Spanish and Polish. This, in turn, is due to the different type of role of Latin in both languages in its early stages of formation. The article ends with the conclusions and a brief reflection about neocultisms.